What Should We Know About Twin to Twin Transfusion Syndrome: A Case Report - Novinka Iriane; Andrieta Berliana Marzani; Angelica Rosa Septiana Hartono; Chris Monalisa; Cindy Thalia Putri; Jessica Natasya; Kevin Axel; Zarahnaya Putri; Sheila Meriyani; Rizna Tyrani Rumanti; Theresia Monica Rahardjo; Aloysius Suryawan (Medical Clinical Update, 2022)
Background Twin-to-twin transfusion syndrome (TTTS) is a condition that can occur as a complication of a monochorionic twin pregnancy that may develop at any stage of pregnancy and most cases are diagnosed in the second trimester of pregnancy. The syndrome is a placental vascular anomaly that can affect the two fetoplacental circulations which can result in hypotony, hypovolemia, anemia, and oliguria being developed in the donor, whereas the recipient fetus is at risk of hypertrophy, hypertension, hypervolemia, polycythemia, and polyhydramnios. Case presentation A 32-year-old multigravida woman (Gravida 5 Para 4 Abortion 0) with a gestational age of 26 weeks came to the Obstetrics and Gynecology Clinic of Unggul Karsa Medika Hospital with the results of the first ultrasound at 24 weeks of gestation which revealed monochorionic diamniotic intrauterine twins and anterior placenta with grade I maturity. Twin A Maturity of 23 weeks 2 days with a fetal weight of 578 grams, oligohydramnios, fetal kidney, and bladder are not visible, whereas Twin B Maturity of 26 weeks 6 days with a fetal weight of 1205 grams, polyhydramnios with a single 12 cm deepest pocket and normal fetal kidney with bladder distention. The diagnosis of twin-to-twin transfusion syndrome was made with twin A as donor twins and twin B as recipient twins. Conclusion TTTS can be diagnosed with routine prenatal ultrasound and can be deferred into 4 stages based on ultrasound and doppler results. There are multiple options for management including expectant management, amnioreduction, intentional septostomy, fetoscopic laser photocoagulation, selective reduction, and voluntary pregnancy termination.